Incorporating genetic criteria into effective ecological restoration (Biocenosis, 2025)
The aim of this review is to highlight the importance of incorporating genetic diversity into ecological restoration and to provide practical recommendations for its effective application. An analysis of the current scientific literature was conducted, including case studies of restoration projects in various degraded terrestrial ecosystems. The review focuses on genetic criteria applied to the selection of plant material, seed provenance, local adaptation, and gene flow, as well as the use of modern genomic tools to support decision-making. The results indicate that considering these criteria enhances the viability, resilience, and functionality of restored populations, and that strategies such as broad seed collection, the use of mixed provenance, and the integration of genetic markers contribute significantly to the success of projects. It is concluded that ecological restoration requires combining genetic criteria with ecological, environmental and social factors, while implementing long-term monitoring and evaluation to ensure sustainable, functional, and adaptable ecosystems in the face of future challenges.
Keywords: ecosystems; genetic diversity; local adaptation; gene flow; climate change